Active integration of electric vehicles into distribution grids: Barriers and frameworks for flexibility services. (July 2021) - Gonzalez Venegas, Felipe; Petit, Marc; Perez, Yannick
Abstract: Distribution system operators face a challenging environment marked by increased decentralization, digitalization, and the decarbonization of transport and heating sectors. In particular, the integration of large numbers of electric vehicles (EVs) will pose challenges for distribution grid operation and planning. However, EVs also open the opportunity to offer flexibility services to different actors in the electricity system using smart charging and vehicle-to-grid (V2G) technology. This work reviewed the scientific literature and key European demonstrator projects on the proactive integration of EVs into distribution grids. The main technical, economic, regulatory, and user-related aspects were analyzed and the associated barriers identified. There is a broad scientific literature on the technical feasibility of EV flexibility provision and coordination schemes, which has as well been proved in demonstrator projects, even though the required technologies for V2G (bidirectional chargers, communication protocols) are not yet widespread. On the other hand, main barriers are economic and institutional, largely due to a lack of regulatory frameworks to value flexibility at distribution level and thus uncertainty on the value of these flexibility services. In particular, this work analyzed four possible value frameworks (grid codes, connection agreements, tariffs and market platforms) to use flexibility at the distribution level, and their implementations with EV fleets in demonstrator projects. Highlights: Holistic review of scientific literature and EV demonstrator projects. Identification of flexibility services that EVs can provide throughout the value chain. Identification of technical, economic and regulatory barriers for active EV integration. Analysis of possible frameworks to use EV-driven flexibility at distribution level.